Nitrogen use efficiency and life cycle of nodules in alfalfa after different mineral fertilization and soil cultivation - V. Vasileva; I. Pachev (Global Journal of Environmental Science and Management)
Nitrogen use efficiency and life cycle of root nodules in alfalfa after different mineral fertilization and soil cultivation practices were studied. Field trial was conducted in the Institute of Forage Crops, Pleven, Bulgaria on leached chernozem subsoil type and no irrigation. The next treatments were tested: i) for fertilization as follows: N0P0K0 (control); N60P100K80 (an accepted technology); N23P100K35 (nitrogen was applied 1/2 in first year of growing and 1/2 in third year); N23P100K35 (nitrogen was supplied pre-sowing); N35P80K50, and Аmophose - 250 kg/ha, calculated at fertilizing rates N27P120K0; ii) for soil cultivation as follows: soil loosing 10-12 cm, plough at depth 12-15 cm, 22-24 cm (an accepted technology), 18-22 cm and 30-35 cm. It was found that soil cultivation and mineral fertilization had effect on nitrogen use efficiency and life cycle of root nodules in Alfalfa. Nitrogen use efficiency was found to be highest at N23P100K35 and plough at the depth of 22-24 cm. Life cycle of root nodules was the longest at N35P80K50 and plough at the depth of 18-22 cm. The better root mass to nodule number ratio was found at N23P100K35 and plough at the depth of 22-24 cm.